Knowledge, attitude, and practices toward evidence-based practice among magnetic resonance radiographers in Klang Valley / Ummu Ilyana Kamarudin, Ann Erynna Lema Thomas Sudin and Faikah Zakaria - Kamarudin, Ummu Ilyana; Thomas Sudin, Ann Erynna Lema; Zakaria, Faikah (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Evidence-based practice (EBP) is defined as combining the best research evidence with clinical experience, as well as patient values and circumstances. In Malaysia, EBP implementation has not been addressed sufficiently among magnetic resonance (MR) radiographers. This study is aimed to assess the knowledge, attitude, and practices (KAP) toward evidence-based practice (EBP) among MR radiographers in Klang Valley. An online questionnaire survey was administered to MR radiographers (n=114) in selected public and teaching hospitals in Klang Valley via social media platforms. The data collected was analyzed using frequencies and chi-square test. Low level of EBP knowledge (n=61, 53.5%) was demonstrated in response to questions about formal training and search strategies, formal training in critical appraisal, the ability to view research critically, locate relevant research and unfamiliarity of the terminology. The MR radiographers (n=110, 96.5 %) had positive attitude and agreed that the use of EBP was required for the procedure. In addition, MR radiographers (n=75, 65.8 %) also had low use and practice of EBP in their daily clinical work. Although most MR radiographers' attitudes toward EBP appeared to be positive, however their knowledge, use, and practice of EBP were underwhelming.